Two operating modes of palladium film hydrogen sensor based on suspended micro hotplate. (23rd April 2019) - Liu, Qi; Yao, Jinyuan; Wu, Yongjin; Wang, Yipin; Ding, Guifu
Abstract: Palladium film hydrogen sensor based on suspended micro hotplate has been fabricated to operate at elevated temperature with low power consumption. Below 150 °C, the response of the sensor to H2 is represented by an increase in resistance. At higher temperature, the phenomenon of resistance reduction appears when it comes into contact with H2 . We have researched the reasons for this phenomenon and proposed that the sensitive mechanism is the redox reaction of Pd film on the suspended structure. The suspended substrate can affect the temperature at which redox of the Pd film occurs, and be sensitive to the changes of the surrounding gas stream. When the working temperature is 400 °C, the magnitude of response (S) changes to −0.4% within 2 s for 200 ppm H2, and S changes to −3% within 10 s for 4000 ppm H2 . This micro hotplate based hydrogen sensor can control the range of operating temperature according to the performance requirements. Highlights: Palladium film hydrogen sensor based on suspended micro hotplate is fabricated to operate with low power consumption. Below 150 °C, the resistance signal of the sensor is increased, and the response time is shortened to about 30 s. At 150 °C or above, the phenomenon of resistance reduction appears because of the sensitive mechanism of redox reaction. Under high temperature operating mode, the response time can be reduced to less than 10 s.